Case Report: A Case of Congenital Nephrogenic Diabetes Insipidus Caused by Thr273Met Mutation in Arginine Vasopressin Receptor 2 - Huang, Li; Ma, Lina; Li, Linjing; Luo, Jiajia; Sun, Tianhong (Frontiers in Pediatrics, 2021)
Congenital nephrogenic diabetes insipidus (CNDI) is a rare hereditary tubular dysfunction caused mainly by X-linked recessive inheritance of AVPR2 gene mutations. Pathogenic genes are a result of mutations in AVPR2 on chromosome Xq28 and in AQP2 on chromosome 12q13. The clinical manifestations of CNDI include polyuria, compensatory polydipsia, thirst, irritability, constipation, developmental retardation, mental retardation, persistent decrease in the specific gravity of urine, dehydration, and electrolyte disorders (hypernatremia and hyperchloremia). Herein, we report a rare case of CNDI caused by an AVPR2 mutation in a 2-year-old Chinese boy who had sustained polyuria, polydipsia, and irritability for more than 20 months. Laboratory examinations showed no obvious abnormality in blood sodium and chloride levels but decreased urine osmolality and specific gravity. Imaging findings were also normal. However, genetic analysis revealed a C>T transition leading to T273M missense mutations in AVPR2. We provided the boy a low-sodium diet and administered oral hydrochlorothiazide and indomethacin for 1 month, after which his clinical symptoms significantly improved. This case report suggests that CNDI is characterized by pathogenic T273M missense mutations alone and expands our understanding of the pathogenesis of CNDI.